Self-medication practice among the general public in Jordan: a cross-sectional study - Abuhamdah, Sawsan M. A.; Naser, Abdallah Y. (Frontiers in Public Health, 2024)
Objectives The phenomenon of self-medication is a noteworthy public health concern that is increasingly prevalent on a global level, particularly in developing nations. This study aims to explore the prevalence of self-medication of over-the-counter (OTC) medications among the general public in Jordan. Materials and methods This cross-sectional online survey study was conducted in Jordan between November and December 2022. An online questionnaire link was distributed to the study participants through social media platforms (Facebook, WhatsApp, and Instagram). The questionnaire tool for this study was adapted from a previously developed questionnaire by Tesfamariam et al. The questionnaire tool comprised four sections that examined participants’ demographic characteristics, knowledge of OTC self-medication, attitudes toward OTC self-medication, and associated practices. Binary logistic regression analysis was used to identify predictors of OTC self-medication practice. Results A total of 1,218 individuals participated in this study. More than half of the study participants (56.9%) confirmed that they were currently using or had in the past year used medication(s) not prescribed by a healthcare specialist. Participants’ agreement level on statements that reflected a positive attitude toward self-medication practice ranged between 13.1 and 33.0%. The statement most commonly agreed with was that ‘OTC medications are safe but I would seek a physician’s advice before using them’ (57.7%). Individuals aged 36–40 years and 51 years and over, those who were married or divorced, those who were employed, and those who had chronic diseases were more likely to practice self-medication compared to others (p < 0.05). Conclusion The current study findings suggest a significant lack of awareness among the general population in Jordan regarding the expected efficacy of OTC medications. A restricted level of agreement was observed among the participants concerning the behavior of self-medication.